Scaling professional development for mathematics teacher educators. (April 2019) - Carney, Michele B.; Brendefur, Jonathan L.; Hughes, Gwyneth; Thiede, Keith; Crawford, Angela R.; Jesse, Dan; Smith, Brandie Ward
Highlights: Description of an apprenticeship-based model for mathematics professional developers. Positively and consistently influenced course participants' knowledge across instructors. Positively influenced course participants' self-efficacy; more variability in change in self-efficacy across instructors.